Trainer Competence in learning Management at the Social Welfare Education and Training Center of the Ministry of Social Affairs - Sri Wuryanti; Ahmad Hudalil; Ika Nugrahaeni (Penerbit Goodwood, 2025)
Purpose: This research aimed to describe the Competence of Lecturers in Managing Learning at the Social Welfare Education and Training Center of the Ministry of Social Affairs. Research methodology: This research was a descriptive research method with a qualitative approach. Data sources were determined by snowball sampling, where the data analysis procedure used was an interactive model from Miles. Results: The Social Welfare Training and Education Center of the Ministry of Social Affairs has implemented learning management competencies as abilities that Widyaiswara must have in planning, compiling, implementing, and evaluating learning concerning Widyaiswara Competency Standards. Limitations: This study has two limitations; 1) It only researched one Widyaiswara competence, namely learning management and not using the substance, personality, and social competencies; 2) Informants only come from the Ministry of Social Welfare Education and Training Center and have not included informants from the Social Welfare Education and Training Center in each region. Contribution: The study's findings are intended to be used to make suggestions to institutions, policymakers and interested parties so that improvements can be made to the implementation of the Education and Training at the Social Welfare Education and Training Center of the Ministry of Social Affairs